The role of libraries in Indigenous language revitalization: A te reo Māori perspective. Issue 1 (1st August 2019) - Lilley, Spencer
Te reo Māori (Māori language) is the Indigenous and an official language of New Zealand. As such it is unique and considered a taonga (treasure) by Māori. It is the language that describes the land and its geographic features, acknowledges the feats of ancestors and is at the core of mātauranga Māori ('Māori knowledge systems'). Although it is not as endangered as other Indigenous languages, te reo Māori continues to struggle for survival due to low levels of fluent speakers. The purpose of this article is to first provide some background about why te reo Māori is considered to be under threat and describe the importance of the revitalization initiatives implemented by the New Zealand government and the Māori education sector. The main body of the article will then focus on the contribution that the New Zealand library and information sector is making to te reo Māori revitalization efforts. This will include descriptions of specific initiatives and an assessment of the impact that these are having on the revitalization process overall. The final part of the article discusses opportunities for future initiatives, and provides information about forthcoming research related to the role that libraries and other cultural institutions have in the revitalization of te reo Māori. In the years after widespread colonization started (1840 onwards), te reo Māori became a language that was repressed through the assimilationist policies and practices of successive governments (Simon 1998; Walker 2004; Winitana 2011). These practices included paying subsidies to mission schools to teach their Māori pupils in English. When Native schools were established in the 1860s, they were expected to teach a curriculum that was based on the English system of education, actively discouraging any aspect of Maori culture and including a preference for the English language. The Native Schools Code of 1880 (Appendix to the Journals of the House of Representatives 1880) further reinforced these practices. Generations of Maori pupils were forbidden from speaking their own language at school. This was reinforced through corporal punishment. Although there was a loosening of the restrictions on cultural elements from the 1930s, te reo Māori continued to be discouraged. Although te reo Māori is now recognized as an academic subject in New Zealand schools, it is not a compulsory subject, nor is it available in every school. By the 1970s, the number of native speakers of te reo Māori had declined to the point where the language was in serious danger of becoming extinct. In the 1980s, Maori-initiated language initiatives led to a range of educational and societal innovations that has helped to rebuild the strength of the language. In order for te reo Māori to survive and recover further from the decades of repression it is necessary for it to be spoken all of the time in a variety of social and educational situations. This involves moving language conversations into everyday contexts, providing opportunities for the speakers of the language (at all levels) to engage and interact with it as a normal practice. As most libraries in New Zealand (except special libraries) are public institutions that attract a high numbers of visitors, they are in a unique position to provide visible evidence of how te reo Māori can enhance and contextualize cultural experiences and understanding. Over the past 30 years, the New Zealand library and information profession have demonstrated a strong commitment to embracing and integrating Mātauranga Māori ('Māori knowledge systems') into their collections and services, including te reo Māori and tikanga Māori ('Māori customary practices'). This article documents how this has been achieved. It will also highlight the opportunities available to continue to improve how libraries and te reo Māori initiatives engage with each other.